PENGGUNAAN MEDIA AJAR BERBASIS MULTIMEDIA DALAM PEMBELAJARAN KANJI - Firmansyah, Dian Bayu; Rahmawati, Riska Sri (Universitas Pendidikan Indonesia (Indonesia University of Education), 2018)
This study aims to determine the effect of the use of teaching media kanji